Penerapan Pembelajaran Tematik di MI Aswaja I Tamban Kedawung Kecamatan Mojo Kabupaten Kediri - Muslimin Muslimin; BT Nikmatul Lailiyah (eL Bidayah: Journal of Islamic Elementary Education, 2019)
Regulation of the Minister of Education and Culture (Permendikbud) No. 64 of 2013 concerning the Content Standards for Primary and Middle Education Units covers the scope of the minimum competency stipulates that the approach in learning in Primary and Secondary Schools is the thematic learning or curriculum 2013. This basis is used as researchers to conduct research on: the application of thematic learning and its results in Primary Islamic School (MI) Tamban Kedawung Mojo, Kediri. This study uses qualitative research with a phenomenological approach that illustrates the experience of each teacher in applying thematic learning in Primary Islamic School (MI) Tamban Kedawung Mojo, Kediri. The data source in this study is the Head of Madrasah, MI Aswaja I Tamban Kedawung teacher taken by observation, interview and documentation techniques. The research instruments used in this study include, observation guidelines and interview guidelines. Data analysis techniques are carried out through three stages, namely: reduction, display and verification/ conclusion. The results showed that: (1) Teachers in planning have not made competency mapping and theme webs. (2) In the implementation, learning has been thematically and the boundaries between the materials are not visible, the methods used at the time of learning also vary. In addition, teachers also use media in the learning process. The types of assessments used by teachers are tests and non-tests. (3) Student learning outcomes are satisfying in each class even though there are some children whose grades are the same as KKM in the class.